The controlled disassembly of mesostructured perovskites as an avenue to fabricating high performance nanohybrid catalysts - Wang, Y.; Arandiyan, H.; Tahini, H.; Scott, J.; Tan, X.; Dai, H.; Gale, Julian; Rohl, Andrew; Smith, S.; Amal, R. (Macmillan Publishers Limited, 2017)
© The Author(s) 2017. Versatile superstructures composed of nanoparticles have recently been prepared using various disassembly methods. However, little information is known on how the structural disassembly influences the catalytic performance of the materials. Here we show how the disassembly of an ordered porous La0.6Sr0.4MnO3 perovskite array, to give hexapod mesostructured nanoparticles, exposes a new crystal facet which is more active for catalytic methane combustion. On fragmenting three-dimensionally ordered macroporous (3DOM) structures in a controlled manner, via a process that has been likened to retrosynthesis, hexapod-shaped building blocks can be harvested which possess a mesostructured architecture. The hexapod-shaped perovskite catalyst exhibits excellent low temperature methane oxidation activity (T90%=438 °C; reaction rate=4.84 × 10−7 mol m−2 s−1). First principle calculations suggest the fractures, which occur at weak joints within the 3DOM architecture, afford a large area of (001) surface that displays a reduced energy barrier for hydrogen abstraction, thereby facilitating methane oxidation.